Clinical significance of acidic extracellular microenvironment modulated genes - Kato, Yasumasa; Mawatari, Kotori (Frontiers in Oncology, 2024)
BackgroundThe extracellular pH (pHe) is known to be acidic. We investigated the effect of mild (pHe 6.8) and severe (pHe 5.9) acidosis on gene expression in mouse B16-BL6 melanoma cells using cDNA microarray analysis and compared them with the acidic pHe dependence of human tumors.MethodsB16-BL6 cells were treated with pHe 7.4 (control), pHe 6.8, and pHe 5.9. The mRNA expression was analyzed by using the cDNA microarray. Heat map, volcano plot, and gene ontology enrichment analysis were performed. The data were compared with the gene signatures of published data GSE52031 and GSE8401 and compared with the pathological staging by GEPIA2, and the prognostic signature of proteins was searched by the Human Protein Atlas database. If the acidic pHe-induced and -reduced genes were correlated with shortened and prolonged survival times, respectively, and also correlated with pathological staging, we defined it as “hit” and counted the sum of hit points of eight types of tumors such as breast, colorectal, prostate, gastric, liver, prostate, lung, and head and neck and melanoma.ResultsGene expression was differentially and commonly regulated by both pHes. The number of genes upregulated fourfold or more at pHe 6.8 and 5.9 only for 25 and 131 genes, respectively, and 85 genes were common. The number of genes downregulated fourfold or less at pHe 6.8 and 5.9 only for 63 and 82 genes, respectively, and 118 genes were common. Compared with human mRNA expression data (GSE8401), there is no correlation with the overall pattern of the signature. In seven types of cancer (breast, colorectal, gastric, liver, prostate, lung, and head and neck) and melanoma, the relationship between acidic pHe-modulated gene expression and overall survival was evaluated. As a result, acidic pHe dependency contributing to prognosis was higher in colorectal, lung, and head and neck cancers and lower in prostate cancer.ConclusionTumor classification based on response to extracellular acidic pHe will provide new insights into chemotherapy strategy for patients with tumors.